The structure and dynamics of human ecosystems : toward a model for understanding and action - Burch, William R., 1933-; Machlis, Gary E.; Force, Jo Ellen (Yale University Press, 2017)
A landmark book that strives to provide both grand theoryand practical application, innovatively describing the structure and dynamics of human ecosystems.